Architecture of outgrowth fungal biofilms as a preliminary step in the biodegradation of polyester-imide enameled copper wires - Júnior, Giancarlo Soncini; Marconato, José Carlos [UNESP]; Martins Franchetti, Sandra Mara [UNESP] (My University, 2011)
Polyesters play an important rule within the group of engineering polymers and arelargely used in several occasions as protective coatings. In the field of electricalinsulation, there is a huge demand for thermal resistant materials and due to this fact, upuntil now, the macromolecules used have been aromatic in nature or are modified withsome heterocyclic structures, as imides or amides groups. Polyester-imides, a thermalresistant class of polymers with important application as electrical insulators, have itsresistance against the microorganisms few studied. These polymers (oligomers withmolar masses below 2.000 g mol-1) are synthesized by the esterification of terephthalicacid and derivates with bi and tri functional glycols. The imidization is conduced by thein-situ reaction of aromatic diamines and aromatic anhydrides. Polyester-imides aredissolved in a mixing of aromatics hydrocarbons and some phenol derivates between 25to 45% non volatiles, depending on the viscosity of the final varnishes. Copper wires areenameled in horizontal or vertical enameling machines. During the cure process, thepolymer achieves a not determinable degree of polymerization and due to the highlyaromatic nature of the polymer and also a residual phenol derivates still remaining in thereticulated polymer, an antifungal activity could be expected. To evaluate the eventualbiodegradation of such polymeric surfaces, a model was developed for studying fungalbiofilms in vitro. As growth was daily monitored, these studies aimed to analyze the great fungi potential present in biodeteration and biodegradation processes, based on the presence of a strongly and well defined biofilm, investigated by scanning electron microscopy. © 2011 by Nova Science Publishers, Inc. All Rights Reserved.
Keywords: Biodegradation; Fungal biofilms; Polyester-imides; Polymers